The influence of processing additives on the processability and properties of styrene-butadiene rubber - D. V. Sitnikova; A. M. Bukanov (Тонкие химические технологии)
Short review devoted to prediction of phase morphologies of heterogeneous polymer blends with the aim of the development of novel composite polymeric materials. The works discussed are performed mainly at the department of chemistry and physics of polymers and polymeric materials.